Driving Forces behind Language Change. Does Danish Theory Hold up in Lithuania? - Vaicekauskienė, Loreta (Scandinavistica Vilnensis, 2019)
The paper presents a large-scale investigation of attitudes towards standard and dialectal speech varieties in Lithuania. It aimed at, firstly, obtaining comparable data on assessments of speech variation under two methodologically different conditions: ‘unaware condition’ (the participants being unaware of the linguistic goals of the research) and ‘aware condition’. Secondly, it aimed at testing whether the two layers of consciousness yield two different systems of social values and how the evaluations accord with changes in language usage. The theory was developed by Danish scholars whose numerous experimental studies proved the driving force role of subconscious attitudes. The investigation closely followed the Danish methodology and was carried out in 23 secondary schools in 7 regions and the capital city of Lithuania, covering almost 1.5 thousand pupils in total. The regularity of the findings, i.e. the overall tendency to overtly valorise local dialects but subconsciously to downgrade dialect accented voices, confirmed that language awareness affects assignment of values to language and must be regarded as an important explanatory factor for the scenarios of language change.
Keywords: language attitudes; speaker evaluation experiment; social values; language change; language variation